Lost in Translation? Openness, Reflexivity and Pragmatism as Guiding Principles for Cross-Language Qualitative Research - Erhard, Franz,Jukschat, Nadine,Sammet, Kornelia (SSOAR, GESIS – Leibniz-Institut für Sozialwissenschaften e.V., 2021)
Abstract: In increasingly globalised and linguistically diverse societies, cross-language constellations in qualitative research are becoming more probable and necessary. Based on experiences we gained during our research in foreign language settings, we reflect on three guiding principles of qualitative research - openness, reflexivity and pragmatism - and how they are applied when dealing with the manifold challenges of linguistic understanding. Taking up ongoing discussions about this issue, we provide an account of a reflexive methodology aware of its preconditions and limitations. We argue in favour of a confident approach towards language difficulties and point out that qualitative research has always demanded the chosen methods to be flexible enough to adjust to challenges in the field
10.17169/fqs-22.3.3722
Keywords: Fremdsprachen; Offenheit; Pragmatismus; Reflexivität; Verstehenslücke; cross-language research; foreign languages; gap of understanding; openness; pragmatism; reflexivity; sprachenübergreifende Forschung; translation; Übersetzung